Performance of Xpert® MTB/RIF among tuberculosis outpatients in Lilongwe, Malawi - Tarsizio Chikaonda; Nelson Nguluwe; Brian Barnett; Runa H. Gokhale; Robert Krysiak; Isaac Thengolose; Nora E. Rosenberg; Christopher Stanley; James Mpunga; Irving F. Hoffman; Mina Hosseinipour; Lesley Scott; et al. (AOSIS, 2017)
Background: Xpert® MTB/RIF is a molecular test for the detection of Mycobacterium tuberculosis and rifampicin resistance. It is considered to be a great advance over smear microscopy and culture. However, there is very little information regarding the performance characteristics of Xpert MTB/RIF in Malawi. Objective: We aimed to evaluate the performance of Xpert MTB/RIF in a Malawian setting. Methods: Stored sputum pellets were processed on Xpert MTB/RIF between June 2012 andMay 2014. Results were compared to mycobacteria growth indicator tube and Löwenstein-Jensen cultures, LED fluorescent microscopy and GenoType® MTBDRplus assay. Rifampicinresistance was confirmed by DNA sequencing. Results: Of the 348 specimens with valid Xpert MTB/RIF results, 129/348 (37%) were smearpositive and 198/348 (57%) were culture-positive. Xpert MTB/RIF demonstrated a sensitivity of 93.8% (95% CI 89.4% - 96.8%) and specificity of 97.4% (95% CI 93.5% - 99.3%), with a positive predictive value of 97.8% (95% CI 94.6% - 99.4%) and a negative predictive value of 92.6% (95% CI 87.4% - 96.1%). Xpert MTB/RIF correctly identified 185/186 (99.5%) rifampicin sensitive and 2/2 (100%) rifampicin-resistant M. tuberculosis strains. Mutations were notdetected by sequencing in one isolate which was rifampicin resistant on Xpert MTB/RIF butsensitive on MTBDRplus. Four non-tuberculous mycobacteria grew from four smear-negativespecimens, namely, M. avium (n = 1) and M. intracellulare (n = 3). No cross-reactivity wasobserved with any of the non-tuberculous mycobacteria when using Xpert MTB/RIF. Conclusion: When fully implemented, Xpert MTB/RIF may have an impact on patient care inMalawi. The increased diagnostic yield of Xpert MTB/RIF over smear microscopy can increaselaboratory-confirmed tuberculosis detection and ensure that treatment is given to appropriateindividuals or groups.